Patient Engagement for the Development of Equity-focused Health Technology Assessment (HTA) Recommendations in the Digital Era - Simeon, Rosiane (Université d'Ottawa / University of Ottawa, 2023)
Background: Health technology assessment (HTA) is a form of policy analysis to inform recommendations for decision-makers. An equity-focused HTA recommendation consists of one that explicitly addresses the impact of health technologies on individuals disadvantaged in society because of their social conditions. However, there is a need for more evidence on the relationships between patient engagement and the development of equity-focused HTA recommendations. Objectives: The objectives of this dissertation were to examine the association between patient engagement and equity-focused HTA recommendations and identify implementation considerations for patient engagement in HTA. Methods: I used explanatory sequential mixed methods to analyze 60 HTA reports and 11 interviews with patients and analysts from Canadian organizations: the Canadian Agency for Drugs and Technologies in Health (CADTH) and Health Quality Ontario (HQO). Results: Quantitative analysis of the HTA reports showed that patient engagement significantly predicts equity-focused HTA recommendations (OR: 0.26; 95% CI: [0.16 – 0.41]). HTA reviews where HTA analysts directly interviewed patients (OR: 3.85; 95% CI: [2.40 – 6.20]) and where an advisory committee used consensus were more likely to contain equity-focused recommendations (OR: 2.27; 95% CI: [1.35 – 3.84]). Qualitative analysis of the interviews identified strategies for engaging diverse patients in HTA. Conclusion: The findings of this dissertation can inform the designing of patient engagement in HTA.
Keywords: Health technology assessment; Patient engagement; Health equity; HTA recommendations; Knowledge-to-action (KTA) cycle; Explanatory case study